Amine Functionalization Within Hierarchically‐Porous Zeotype Framework for Plasmonic Catalysis over PdAu Nanoparticles. Issue 4 (16th January 2023) - Verma, Priyanka; Mori, Kohsuke; Kuwahara, Yasutaka; Manzoli, Maela; Morandi, Sara; Fukuhara, Choji; Raja, Robert; Yamashita, Hiromi
Abstract: Plasmonic catalysis has revealed improved product yield and selectivity in various chemical transformation reactions over the past decade. In this report, the effect of tertiary amine (‐NR3 ) functionalization on the surface of hierarchically‐porous zeotype (HP‐AlPO‐5) materials to enhance the plasmon‐mediated catalysis, utilizing a combination of the plasmonic antenna (Au) and catalytic reactor (Pd) nanoparticles (NPs) was investigated. The catalysts have been characterized using enhanced techniques such as HAADF‐STEM, FT‐EXAFS, and probe‐based FT‐IR to reveal the proximity and interaction between bimetallic NPs, and thermal stability of amines in the presence of Au or PdAu NPs. Interestingly, a four‐fold enhancement in the Suzuki‐Miyaura coupling reaction product yield was obtained over PdAu/HP‐AlPO‐5‐NR3 when compared with the analogous plasmonic catalyst with no amine functionalization under visible light irradiation. A range of amines were functionalized and their influence in the nucleation, uniform growth and stabilization of catalytic active site (Pd) and formation of electron‐rich species under visible light irradiation has also been investigated. The presence of tertiary amine in the nanostructured catalyst enhanced the turnover number (TON) significantly under light irradiation conditions in comparison to dark conditions. This study provides an enriched understanding of plasmon‐driven chemistry, where the maximized reaction rate enhancement requires the existence of active metal species and the formation of electron‐enriched species under light irradiation conditions. Abstract : Plasmonic catalysis : Influence of tertiary amine functionalization on the surface of hierarchically‐porous zeotype materials to enhance the plasmon‐mediated catalysis, utilizing a combination of the plasmonic antenna and catalytic reactor nanoparticles.